Tradition Mills’ Picholine Olive Oil Physicochemical Characterization and Chemical Profiling across Different Cities in Morocco - Hamza El Moudden; Yousra El Idrissi; Chakir El Guezzane; Walid Belmaghraoui; Adil El Yadini; Hicham Harhar; Mohamed Tabyaoui (The Scientific World Journal)
This study aims to determine the quality of olive oils (Picholine variety) from the traditional oil mills in different Moroccan cities by means of physicochemical characterization and chemical compositions. All samples of olive oil were collected from traditional oil mills. Physicochemical analyses of free fatty acid (FFA), iodine value (IV), saponification value (SV), specific extinction at 232 and 270 (E232, E270), chlorophyll content, carotenoid content, fatty acids (FAs), and total phytosterols composition were performed with respect to the International Olive Council (IOC) standards. These oils were revealed to be rich in unsaturated fatty acids (UFAs): C18 : 1, C18 : 2, and C18 : 3, and that the total phytosterols content ranged between 142.68 and 208.72 mg per 100 g of oil. Also, the chlorophyll contents, for most of the studied samples, are less than 2 mg/kg, while the carotenoid content varied between 0.13 and 0.63 mg/kg. These results, along with the physicochemical assays, helped classify the oils studied into three categories: extra virgin, virgin, and ordinary virgin olive oils. These results confirm that the conditions under which olive oils are collected, pressed, and stored influence the quality of the oil produced. Therefore, there is a need to inform producers about the correct practices and techniques for storage, processing, and conservation of oils to better improve the quality of the final product.